THE EXPERIENCES OF SOCIAL WORKERS IN THE PROVISION OF FAMILY PRESERVATION SERVICES - Nhedzi, Felistas; Makofane, Mankwane (Social Work/Maatskaplike Werk, 2015)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">This paper discusses the experiences of twelve social workers as providers of family preservation services. The sample was selected through purposive and snowball sampling. Data were collected through face-to-face semi-structured interviews, which yielded rich information on a host of challenges experienced by social workers. Some of the challenges entail the parents’ reluctance to participate in family preservation services, their unwillingness to care for their children, non-adherence to intervention plans, protection of perpetrators of child abuse by family members, traditional practices, lack of resources and low salaries.<span style="font-family: ’Times New Roman’,’serif’; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> These challenges have an adverse effect on the morale and wellbeing of social workers